Harmoni Bahasa dari Persfektif Penerjemahan dalam Kasus Pemadanan Istilah Teknis - Muhamad Nur (Badan Pengembangan dan Pembinaan Bahasa, 2017)
The language harmony in this study is oriented to the idea of the awakening of sincronized or similar object, concept, definition and term in relation to the terms adoption strategy by a general translation from one language to another (donor by recipient language). Terms are important pillars in the science systems that they must have the same meaning for everyone using it so the information exchange will obtain a good result. Thus, through a general consensus on meanings, names and specific terms along with the usages consistently will result in the uniformity of a special vocabulary containing the standard concepts, terms and definitions. The data collecting method is by browsing electronic library (e-lib) with data source taken as samples such as (1) Phonological adaptation of borrowed terms in Duramazwi reMimhanzi, (2) Translation journal of translation procedures, strategies and methods, (3) Are there connections between English and Romanian terminology in Medicine?, (4) Third-year students’ difficulties in translating computing terms from English into Arabic, (5) Studying Loanwords and Loanword Integration: Two Criteria of confirmity. The analysis is conducting by observing phonological aspects phenomenon (concerning pronunciation system) and orthographic aspect (concerning writing system). Based on these data, it is shown that the technical term equivalence strategy is conducted through the adjustment of sound and the foreign writing system (donor language) with changes based on the phonological system according to the pronunciation and the orthography system of a language (recipient language). The strategy is an attempt to maintain the full meaning of the concept contained in the terms of a language which meaning is not revealed in other languages in order to establish harmony or similarity of vision in the context of the use of the term to build language harmony among language speakers or users. AbstrakIstilah merupakan sendi penting di dalam sistem ilmu pengetahuan, harus mempunyai makna yang sama bagi semua orang yang menggunakannya, agar pertukaran informasi memperoleh hasil yang baik, maka melalui kesepakatan umum tentang makna, nama dan istilah khusus serta penggunaannya secara konsisten akan menghasilkan keseragaman suatu kosa kata khusus yang memuat konsep, istilah, dan definisinya yang baku.Artikel ini merupakan hasil kajian bidang penerjemahan tentang suatu pendekatan yang terkait dengan peristilahan, khususnya istilah teknis (technical terms). Sejumlah pendekatan yang dapat disajikan adalah sebagai alternatif dengan mengacu pada prinsip-prinsip kesamaan konsep antara bahasa sumber dan bahasa target (donor and recipient language). Data dalam kajian ini diperoleh melalui akses internet (online) untuk memperoleh jurnal, artikel dan referensi lain yang mengkaji masalah peristilahan dan aspek-aspek linguistik secara tekstual yang berorientasi pada bidang penerjemahan. Hasil dari kajian ini menunjukkan bahwa bentuk interakasi di antara berbagai bahasa dalam bidang penerjemahan, khususnya menyangkut istilah teknis dapat dilakukan dengan pendekatan penyesuaian aspek kebahasaan atau kaidah linguistik bahasa donor menurut aspek atau kaidah kebahasaan bahasa penerima (recipient language). Hal ini dilakukan adalah sebagai upaya untuk mempertahankan makna konsep yang dimiliki bahasa donor di satu sisi, dan upaya menyesuaikan aspek atau kaidah linguistik menurut bahasa penerima di sisi lain. Dengan demikian, harmoni bahasa dapat terbangun bagi penutur atau pengguna bahasa di antara komunitas bangsa itu sendiri.